Variation in the Accumulation of Seed Storage Protein Among Genotypes of Phaseolus vulgaris (L.) - Mutschler, Martha A. (1980)
Differences in the accumulation of total seed protein and globulin-1 (G1) protein were detected among three inbred lines of common bean. Total protein accumulation ranged from 2.3 to 3.7 milligrams per cotyledon pair per day among lines. In all lines the dry weight and protein accumulation ceased and a loss of chlorophyll in the cotyledons occurred when the moisture content had fallen to 50% of fresh weight. G1 was first detected and rapid accumulation began 14 days after flowering in two lines, whereas in the cultivar Endogava zurundi namame, rapid accumulation was delayed until 20 days after flowering. Rates of G1 accumulation ranged from 1.0 to 1.8 milligrams G1 per cotyledon pair per day among lines. G1 accumulation ceased 6 days before the end of total protein accumulation in Sanilac. A steady rate of protein accumulation was observed in Sanilac, but pauses in the accumulation of G1 and of total protein were documented in Endogava zurundi namame. The rate of G1 accumulation preceding and following the pause in Endogava zurundi namame was 2.7 milligrams G1 per cotyledon pair per day, nearly double that of the other lines.